2000
DOI: 10.1177/00912700022009459
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tangential Visual Symbols to Increase the Long‐Term Learning Process: Applications of Linkage in Teaching Pharmacological Principles of Addiction

Abstract: Medieval and Renaissance teaching techniques using linkage between course content and tangentially related visual symbols were applied to the teaching of the pharmacological principles of addiction. Forty medical students randomly divided into two blinded groups viewed a lecture. One lecture was supplemented by symbolic slides, and the second was not. Students who viewed symbolic slides had significantly higher scores in a written 15-question multiple-choice test 30 days after the lecture. These results were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In tasks involving recall, participants have been able to correctly identify 85%-95% of a set of previously presented graphical symbols, whereas recall for words was significantly lower, particularly in larger learning sets (Standing, 1973). A similar advantage was reported by Muter and Mayson (1986), who found that error rates were halved when users were presented with symbols rather than with text; more recently, Giannini, Giannini, and Condon (2000) found that the presentation of symbolic slides during lectures facilitated improvements in the test scores of students.…”
mentioning
confidence: 61%
“…In tasks involving recall, participants have been able to correctly identify 85%-95% of a set of previously presented graphical symbols, whereas recall for words was significantly lower, particularly in larger learning sets (Standing, 1973). A similar advantage was reported by Muter and Mayson (1986), who found that error rates were halved when users were presented with symbols rather than with text; more recently, Giannini, Giannini, and Condon (2000) found that the presentation of symbolic slides during lectures facilitated improvements in the test scores of students.…”
mentioning
confidence: 61%